Phase separation of Hippo signalling complexes. (20th February 2023) - Bonello, Teresa T; Cai, Danfeng; Fletcher, Georgina C; Wiengartner, Kyler; Pengilly, Victoria; Lange, Kimberly S; Liu, Zhe; Lippincott‐Schwartz, Jennifer; Kavran, Jennifer M; Thompson, Barry J
Abstract: The Hippo pathway was originally discovered to control tissue growth in Drosophila and includes the Hippo kinase (Hpo; MST1/2 in mammals), scaffold protein Salvador (Sav; SAV1 in mammals) and the Warts kinase (Wts; LATS1/2 in mammals). The Hpo kinase is activated by binding to Crumbs‐Expanded (Crb‐Ex) and/or Merlin‐Kibra (Mer‐Kib) proteins at the apical domain of epithelial cells. Here we show that activation of Hpo also involves the formation of supramolecular complexes with properties of a biomolecular condensate, including concentration dependence and sensitivity to starvation, macromolecular crowding, or 1, 6‐hexanediol treatment. Overexpressing Ex or Kib induces formation of micron‐scale Hpo condensates in the cytoplasm, rather than at the apical membrane. Several Hippo pathway components contain unstructured low‐complexity domains and purified Hpo‐Sav complexes undergo phase separation in vitro . Formation of Hpo condensates is conserved in human cells. We propose that apical Hpo kinase activation occurs in phase separated "signalosomes" induced by clustering of upstream pathway components. Synopsis: The conserved Hippo signalling pathway regulates the activity of Yorkie (YAP/TAZ in mammals) transcriptional co‐activator via Hippo (MST1/2) and Warts (LATS1/2) kinases. This study shows that Hippo pathway components form large cytoplasmic punctae in epithelial cells through a process that involves the formation of biomolecular condensates. Formation of Hippo kinase condensates is promoted by apically localised upstream signalling components such as Kibra or Expanded. Mechanical strain at the apical domain of epithelial cells inhibits Hippo kinase condensate formation. Hippo kinase condensate formation is inhibited by growth factor signalling via the PI3K‐Akt pathway. The organisation of Hippo kinase complexes into condensates and their regulation is conserved between Drosophila and mammalian epithelia. Abstract : Mechanical strain and growth factor signalling regulate the condensation of Hippo pathway components in Drosophila and mammalian epithelia.